Empowering women through participatory action research in community-based disaster risk reduction efforts. (December 2020) - Ruszczyk, Hanna A.; Upadhyay, Bijay Krishna; Kwong, Yim Ming (Connie); Khanal, Omkala; Bracken, Louise J.; Pandit, Sushil; Bastola, Rajat
Abstract: The role of women in community-based disaster risk reduction efforts (CBDRR) is an area of limited academic research and continues to be a thorny issue for policy and practice. This research paper describes a comparative case study of participatory action research (PAR) in CBDRR conducted in one rural and one urban tole (neighbourhood) of Kathmandu Valley, Nepal. PAR is not a method, rather it is a set of principles guiding research. The "Empowering Women through CBDRR" PAR was motivated by the National Society for Earthquake Technology-Nepal's (NSET) desire to learn how to effectively empower women in disaster risk reduction on a local level and to enhance resilience to everyday hazards and risks as well as earthquakes. The hazards identified by residents in rural Bhainse were the supply of drinking water and landslides while the supply of drinking water and earthquakes were the perceived hazards in urban Tajhya Tole. The small-scale mitigation activities chosen and implemented by the female led disaster risk management groups in partnership with the local authorities and NSET addressed everyday risks (fire) that were important to the community or were related to livelihood concerns (landslide and drainage pipe). While there is clear evidence of women's empowerment and capacity building, sustainability of initiatives is particularly dependent on the commitment of local authorities to incorporate the initiatives into local policies and actions. A gap remains between aspirations to practice empowerment of women and implementation. In many ways, 'doing' empowerment remains problematic in CBDRR.